Professional identity and professional preferences in students of administration from a private university at Arequipa - Callata, Margaret (2017)
This study analyzes and describes the relationship between the professional identity and occupational preferences, in the students of administration of St. Pablo Catholic University. For this, we used the Questionnaire instruments of Professional Identity of Walter Arias and the Inventory of occupational preferences of José Luis Pereira. The sample consisted of 117 students in ninth and tenth semester of the academic year 2015-I.They were obtained as results that only 27% of students in the sample have a preference for management. Comparative, descriptive and analysis of correlation of the data collected are also presented.